Oxidized Carbon Nitrides: Water‐Dispersible, Atomically Thin Carbon Nitride‐Based Nanodots and Their Performances as Bioimaging Probes. Issue 16 (11th March 2015) - Oh, Junghoon; Yoo, Ran Ji; Kim, Seung Yeon; Lee, Yong Jin; Kim, Dong Wook; Park, Sungjin
Abstract Three‐dimensional (3D) carbon nitride (C3N4)‐based materials show excellent performance in a wide range of applications because of their suitable band structures. To realize the great promise of two‐dimensional (2D) allotropes of various 3D materials, it is highly important to develop routes for the production of 2D C3N4 materials, which are one‐atom thick, in order to understand their intrinsic properties and identify their possible applications. In this work, water‐dispersible, atomically thin, and small carbon nitride nanodots were produced using the chemical oxidation of graphitic C3N4. Various analyses, including X‐ray diffraction, X‐ray photoelectron, Fourier‐transform infrared spectroscopy, and combustion‐based elemental analysis, and thermogravimetric analysis, confirmed the production of 3D oxidized C3N4 materials. The 2D C3N4 nanodots were successfully exfoliated as individual single layers; their lateral dimension was several tens of nanometers. They showed strong photoluminescence in the visible region as well as excellent performances as cell‐imaging probes in an in vitro study using confocal fluorescence microscopy.